2014
DOI: 10.1007/s00192-014-2478-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for obstetric anal sphincter injuries and postpartum anal and urinary incontinence: a case–control trial

Abstract: Women with Asian or Indian ethnicity, operative vaginal birth, persistent occipito-posterior position and rapid uncontrolled delivery of the fetal head were likely to sustain OASIS. Awareness of these factors may help to minimise the incidence of OASIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
1
17
1
2
Order By: Relevance
“…It has been reported that a longer second stage of labor is associated with increased risk of OASIS, although other studies have suggested it does not affect the risk . In our study, the singleton group had lower rates of prolonged labor compared to twins.…”
Section: Discussioncontrasting
confidence: 58%
“…It has been reported that a longer second stage of labor is associated with increased risk of OASIS, although other studies have suggested it does not affect the risk . In our study, the singleton group had lower rates of prolonged labor compared to twins.…”
Section: Discussioncontrasting
confidence: 58%
“…9 OASIS have been linked with a number of long-term complications such as faecal incontinence, urinary incontinence, perineal pain, dyspareunia, embarrassment and low self-esteem. 10 Instrumental delivery, increasing birthweight and prolonged second stage are all recognised risk factors for OASIS; 6,8,[11][12][13][14] however, the role of ethnicity remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Obstetric trauma is the primary risk factor for pelvic floor injury, 17 and studies have identified specific obstetric risk factors associated with increased risk of pelvic floor injury. Epidural use in labor has consistently been shown to be either not associated with [18][19][20][21][22] or protective against 23 pelvic floor injury, likely because epidural analgesia relaxes the pelvic floor, decreasing striated muscle stress, and the risk of tearing injury. 17 The association between early epidural use and lower fetal station in active labor in our study may be explained by increased relaxation of pelvic floor musculature among women with epidural analgesia prior to active labor.…”
Section: Discussionmentioning
confidence: 99%